Economic Analysis for Setting Appropriate Repair Cycles on the Fixed Materials and Facilities in the Public Rental Housing - Sung-Min Choi; Yeon-Sil Lee (Advances in Materials Science and Engineering)
Currently, repair and maintenance cycles that follow the completion of construction facilities lead to the necessitation of subsequent data on the analysis of study and plan for maintenance. As such, an index of evaluation was drafted and a plan of maintenance cycle was computed using the investigation data derived from surveying target housing units in permanent rental environmental conditions, with a minimum age of 20 years, and their maintenance history. Optimal maintenance and replacement methods were proposed based on this data. Economic analysis was conducted through the Risk-Weighted Life Cycle Cost (RWLCC) method in order to determine the cost analysis of maintenance life cycle methods used for repair. Current maintenance cycle methods that have been used for 20 years were also compared with alternative maintenance cycles.